Comparison of the microstructure and phase stability of as-cast, CAD/CAM and powder metallurgy manufactured Co–Cr dental alloys. Issue 12 (December 2015) - Li, Kai Chun; Prior, David J.; Waddell, J. Neil; Swain, Michael V.
Highlights: Co–Cr alloys were produced from cast, CAD/CAM and powder metallurgy techniques. Microstructure, crystal structure and chemical composition were analyzed. Fcc phase stability was dramatically higher for alloys with finer grain sizes. Cr content at the alloy surface was higher for finer grained alloys. Phase transformation mechanisms were different between the bulk and interface. Abstract: Objective: The objective of this study was to identify the different microstructures produced by CC, PM and as-cast techniques for Co–Cr alloys and their phase stability following porcelain firings. Methods: Three bi-layer porcelain veneered Co–Cr specimens and one monolithic Co–Cr specimen of each alloy group [cast, powder metallurgy (PM), CAD/CAM (CC)] were manufactured and analyzed using electron backscatter diffraction (EBSD), energy dispersive spectrometry (EDS) and X-ray diffraction (XRD). Specimens were treated to incremental numbers of porcelain firings (control 0, 5, 15) with crystallographic data, grain size and chemical composition subsequently obtained and analyzed. Results: EBSD datasets of the cast alloy indicated large grains >200 μm whereas PM and CC alloy consisted of mean arithmetic grain sizes of 29.6 μm and 19.2 μm respectively. XRD and EBSD results both indicated the highest increase in hcp content (>13 vol%) for cast Co–Cr alloy after treatment with porcelain firing while PM and CC indicated <2 vol% hcp content. A fine grain interfacial layer developed on all surfaces of the alloy after porcelain firing. The depth of this layer increased with porcelain firings for as-cast and PM but no significant increase ( p  > .05) was observed in CC. EDS line scans indicated an increase in Cr content at the alloy surface after porcelain firing treatment for all three alloys. Significance: PM and CC produced alloy had superior fcc phase stability after porcelain firings compared to a traditional cast alloy. It is recommended that PM and CC alloys be used for porcelain-fused-to-metal restorations.